Strengthening the role of relationship management in sustainable employee engagement at selected maritime firms in Nigeria - Adeniji, Chinyerem; Joel, Opeyemi Olunike; Ayankola, Temitope; Adesanya, Oluwatoyin; Efe-Imafidon, Emmanuel (International Journal of Innovative Research and Scientific Studies, 2024)
Relationship management in a maritime firm is essential for maintaining strong partnerships ensuring smooth operations and driving business success within the industry. Extant literature suggests that Nigerian maritime firms must still thoroughly investigate relationship management possibilities and sustainable employee engagement. As a result, this study explores how relationship management affects employee engagement at selected Nigerian maritime companies. 410 respondents were polled from the employees of the selected marine enterprises in Nigeria using a stratified and purposeful sampling technique. Smart PLS 3.0 was used to analyze the returned and valid 380 copies of the questionnaire which provided a response rate of 92.6%. The study’s findings demonstrated that relationship management impacted employees’ cognitive, affective and behavioural engagement. The findings also revealed that behavioural engagement encompassing dedication, enthusiasm and initiative in fulfilling job duties and advancing organizational objectives is the weakest predictor of employee engagement. This suggests a widespread belief that fostering "cultural diversity and unity" in a global workplace is crucial to inspire employees’ engagement and passion for their work. This study offers valid evidence in support of its conclusion that relationship management stimulates the cognitive, affective and behavioural engagement of employees in the Nigerian maritime industry. The study recommends to maritime companies that recognizing diversity and unity in relationship management is essential for higher employee engagement and involvement levels.